2018
DOI: 10.1164/rccm.201707-1457oc
|View full text |Cite
|
Sign up to set email alerts
|

Face Masks and Cough Etiquette Reduce the Cough Aerosol Concentration of Pseudomonas aeruginosa in People with Cystic Fibrosis

Abstract: Funding support: The study was funded by grants from Cystic Fibrosis Foundation Therapeutics USA (BELL14AO) and The Prince Charles Hospital Foundation (MS2014-20). T.J.K. acknowledges National Health and Medical Research Council (NHMRC) Early Career (GNT1088448) and ERS-EU RESPIRE2 Marie Sklodowska-Curie Postdoctoral Research (#4571-2013) Fellowship support. L.D.K. acknowledges an NHMRC Early Career Fellowship (APP1036620) List ONE descriptor number that best classifies the subject of your manuscript: 9.17 Cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 42 publications
11
54
2
1
Order By: Relevance
“…Third, the distance that viable P. aeruginosa cough aerosols could travel in patients with bronchiectasis, COPD or CF was similar (4 m); however, the duration that P. aeruginosa cough aerosols could remain suspended in the air was shorter in patients with bronchiectasis at 15 min compared to 45 min for patients with CF . Finally, the mean concentration of P. aeruginosa in sputum in the bronchiectasis and COPD cohort did not correlate with the total aerosol count observed at 2 m, and this was in contrast to our findings in the CF cough aerosol studies …”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Third, the distance that viable P. aeruginosa cough aerosols could travel in patients with bronchiectasis, COPD or CF was similar (4 m); however, the duration that P. aeruginosa cough aerosols could remain suspended in the air was shorter in patients with bronchiectasis at 15 min compared to 45 min for patients with CF . Finally, the mean concentration of P. aeruginosa in sputum in the bronchiectasis and COPD cohort did not correlate with the total aerosol count observed at 2 m, and this was in contrast to our findings in the CF cough aerosol studies …”
Section: Discussioncontrasting
confidence: 94%
“…Interestingly, our study found 4 of the 20 participants produced cough aerosols containing other GNB. This was a higher proportion than in our previous CF P. aeruginosa cough aerosol studies which is likely to be related to the difference in infection profile in patients with bronchiectasis and COPD compared with CF populations. Incidentally, we found two study participants with bronchiectasis who were high producers of H. influenzae cough aerosols, a common respiratory pathogen of patients with bronchiectasis and COPD .…”
Section: Discussioncontrasting
confidence: 63%
“…Where the organism was detected in sputum samples, a Pearson’s correlation examined correlations between sputum and total viable aerosol at 2 m for each of the GNB and S. aureus organisms detected. The 2 m distance was selected in accordance with the current infection control recommendations for separation between people with CF6 and correlation data for P. aeruginosa from our recent study was also reported as a comparison 7…”
Section: Methodsmentioning
confidence: 99%
“…Potentially infectious bacterial aerosols generated during coughing were dramatically reduced (to 5% of the bacterial concentrations seen during unmasked cough) suggesting short‐term benefit of mask wearing. Talking without a mask led to minimal bacterial contaminated aerosols The role of droplet nuclei transmission of other pathogens is supported by limited evidence and is summarized below: Influenza and other respiratory viruses may be associated with pulmonary exacerbations of CF .…”
Section: Risk Of the Spread Of Organisms From Hcwcf To Others In The mentioning
confidence: 99%
“…However, the majority of CF centres in Australia and New Zealand have implemented or are actively considering implementing similar policies for the care of their patients with CF. Recent data from Queensland have confirmed that talking is a low‐risk activity in terms of generating potential infectious aerosols . However, it is important that wearing surgical mask be considered when HCWcf working in a clinical setting are unable to control their cough.…”
Section: General Infection Control Principlesmentioning
confidence: 99%